Analysis of Pregnancy Characteristics and Perinatal Outcome of Mediastinal Uterus in China - Na Zhang; Ying Wang; Li Zhang; Chanyun Xiao (Tehran University of Medical Sciences, 2021)
Background: To analyze the complications and outcome of mediastinal uterine pregnancy, and put forward targeted prevention and treatment measures. Methods: A total of 248 pregnant women with mediastinal uterus treated were enrolled from Jan 2015 to Dec 2018 in the Maternal and Child Health Hospital of Hubei Province, China. The data, including complications of pregnancy, gestational weeks, mode of delivery, postpartum hemorrhage, placental condition and perinatal prognosis, were collected and analyzed. Results: There were 12 cases with abnormal fetal position in the previous cesarean section. The total number of cases with abnormal fetal position was 99(49.75%). For women with abnormal fetal position during mediastinal uterine pregnancy, there was a significant increase in the incidence of placental abruption (P<0.05). The average gestational age at termination of pregnancy was 37+5weeks. There were 55 cases (22.18%) of premature and 49 cases (19.75%) of premature rupture of membranes, including 29 cases of abnormal fetal position and premature rupture of membranes, mediastinal uterus preterm birth, premature rupture of membranes (P<0.05). There were 13 cases (5.24%) of postpartum hemorrhage, natural birth without neonatal asphyxia, five cases (2.02%) of neonatal asphyxia, preterm birth, and 51 cases (20.56%) of placental adhesion. Of these, 37 cases were cesarean, 13 were spontaneous production, and 71 were fetal umbilical cord winding. Conclusion: The pregnancy induced spontaneous abortion, premature delivery, premature rupture of membranes and abnormal fetal position in mediastinal uterus are significantly higher than normal pregnancy. The complications during delivery are significantly higher than in normal pregnant women.